Omega 1 - Lewis, Mark Edward; LEM Studio Productions; Leomark Studios (Firm) ([Inglewood, Calif.] : LEM Studio Productions, 2013)
In the year 2022, the planet is ravaged by humanity's worst fear: World War III. But this is not a war of bombs and bullets, it is a war of information and governments and the global corporate sector has had no success in finding the leader of the attack, IBRAHIM ANWAR (40s, Middle Eastern). After twenty years of waiting, REV. DR. MICHAEL BERTRAND (50s, Caucasian), the head of a super-secret UN facility, ETHOS, designated to train the world's most genetically perfect children to become an elite fighting force, finally receives his shot at saving the world. With his now mid-twenties wards who are hyper fast, can dodge bullets, draw metal objects to themselves and can strategize better than a five-star general, he sets about searching and destroying the hacker hubs and eventually ending the global extortion of the "Hacker War." None of these super elite warriors are better than the beautiful OMEGA (early 30s, Romanian). But when the bickering between ETHOS siblings escalates, Ibrahim takes command of the situation and is able to use his hacking technology to turn the ETHOS warriors on each other. Omega is able to break the spell, only to have to fight the forces of Ibrahim but also those of her sibling-equals.
Originally released as a motion picture in 2013
Voices: Alina Andrei. Mark Edward Lewis, Jan Shiva, Teresa Noreen.
Editor, Mark Edward Lewis ; music, Mark Edward Lewis.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 8, 2017).
Keywords: World War III -- Fiction; Animated films; Science fiction films; Internet videos; Streaming video